MZC Gel Inhibits SHIV-RT and HSV-2 in Macaque Vaginal Mucosa and SHIV-RT in Rectal Mucosa. (1st March 2017) - Calenda, Giulia; Villegas, Guillermo; Barnable, Patrick; Litterst, Claudia; Levendosky, Keith; Gettie, Agegnehu; Cooney, Michael L.; Blanchard, James; Fernández-Romero, José A.; Zydowsky, Thomas M.; Teleshova, Natalia
Abstract : Abstract: The Population Council's microbicide gel MZC (also known as PC-1005) containing MIV-150 and zinc acetate dihydrate (ZA) in carrageenan (CG) has shown promise as a broad-spectrum microbicide against HIV, herpes simplex virus (HSV), and human papillomavirus. Previous data show antiviral activity against these viruses in cell-based assays, prevention of vaginal and rectal simian–human immunodeficiency virus reverse transcriptase (SHIV-RT) infection, and reduction of vaginal HSV shedding in rhesus macaques and also excellent antiviral activity against HSV and human papillomavirus in murine models. Recently, we demonstrated that MZC is safe and effective against SHIV-RT in macaque vaginal explants. Here we established models of ex vivo SHIV-RT/HSV-2 coinfection of vaginal mucosa and SHIV-RT infection of rectal mucosa in macaques (challenge of rectal mucosa with HSV-2 did not result in reproducible tissue infection), evaluated antiviral activity of MZC, and compared quantitative polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay readouts for monitoring SHIV-RT infection. MZC (at nontoxic dilutions) significantly inhibited SHIV-RT in vaginal and rectal mucosas and HSV-2 in vaginal mucosa when present during viral challenge. Analysis of SHIV-RT infection and MZC activity by 1-step simian immunodeficiency virus gag quantitative RT-PCR and p27 enzyme-linked immunosorbent assay demonstrated similar virus growth dynamics and MZC activity by both methods and higher sensitivity of quantitative RT-PCR. Our data provide more evidence that MZC is a promising dual compartment multipurpose prevention technology candidate.